A methodology of integrating marketing with engineering for defining design specifications of new products - Kwong, C.; Chen, Y.; Chan, Kit Yan (Taylor & Francis, 2011)
In the fuzzy front end stage of new product development, it is quite common that marketing personnel and product engineers have different goals and concerns. Their two sets of goals and concerns are always addressed in isolation from one another. This isolation typically would not result in optimal design decisions as two sets of goals and concerns are always interrelated. Therefore, it is important to integrate the concerns of marketing personnel with those of engineers in defining design specifications. Perceptual mapping is a very common technique used by marketing personnel to understand market positions of competitive products and help define new product opportunities. Although quite a few research works have been attempted to integrate marketing with engineering concerns for new product design, perceptual mapping was not considered in defining design specifications of a new product in the previous related studies. In this paper, a methodology of integrating marketing with engineering for defining design specifications of new products is described, which mainly involves generation of perceptual maps, generation of fuzzy regression models for relating customer requirements and design attributes, formulation of an optimisation model and solving the model based on genetic algorithms. A case study of defining design specifications of a new packing machine was used to illustrate the proposed methodology.